'Beautiful, plain objects like [SKF] ball bearings': The Enigma of Aestheticizing Anonymity in 'Machine Art' and Modernist Logotypes. (18th February 2022) - Shales, Ezra
Abstract: The SKF ball bearing on display in the 1934 'Machine Art' exhibition in the Museum of Modern Art is an icon referenced throughout visual culture studies but this article recognizes its materiality, identifying the corporate logotype and other branded markings that complicate its identity as anonymous or, in the words of museum curator Philip Johnson, as 'plain'. SKF, Svenska Kullagerfabriken (The Swedish ball bearing factory), had a fully developed global advertising campaign that made it a more established brand name than MoMA, and pioneered the contemporary mode of speaking and thinking in logotypes—by 1934, Johnson's claim notwithstanding, no one could 'see' an SKF ball bearing without seeing the company's logo. Scholarly commentary has adhered to MoMA's description as if the bearing were anonymous and not visibly branded. This essay describes the history of the SKF logotype and situates it as both pioneering and part of a complex corporate culture and aspect of brand standardization that intersected with globalization in unexpected ways. To delve into the commercial context and production of ball bearings is to unravel the contradictions inherent in identifying design as national or global, and the modernist idealization of anonymous industrial form as an aesthetic ideal.